Population-specific influence of SLC2A9 genotype on the acute hyperuricaemic response to a fructose load. Issue 11 (24th January 2013) - Dalbeth, Nicola; House, Meaghan E; Gamble, Gregory D; Horne, Anne; Pool, Bregina; Purvis, Lauren; Stewart, Angela; Merriman, Marilyn; Cadzow, Murray; Phipps-Green, Amanda; Merriman, Tony R
Abstract : Background: SLC2A9 is a strong genetic risk factor for hyperuricaemia and gout. SLC2A9 (GLUT9) is a high capacity urate transporter and reportedly transports glucose and fructose. Intake of fructose-containing beverages is associated with development of hyperuricaemia and gout. Objective: To determine whether genetic variation in SLC2A9 influences the acute serum urate response to a fructose load. Methods: Following an overnight fast, 76 healthy volunteers (25 Māori, 26 Pacific, 25 European Caucasian) drank a solution containing 64 g fructose. Serum and urine were obtained immediately before and then 30, 60, 120 and 180 min after ingestion. The SLC2A9 single nucleotide polymorphism (SNP) rs11942223 was genotyped and data were analysed based on the presence or absence of the gout protective minor allele (C). Results: The rs11942223 C allele was present in 17 participants (22%). In the entire group, fructose intake led to an increase in serum urate, which peaked 60 min following fructose ingestion (analysis of variance p=0.006). The presence of the C allele was associated with an attenuated hyperuricaemic response (p(SNP)<0.0001) and increased fractional excretion of uric acid (FEUA) (p(SNP)<0.0001) following the fructose load. The effects of rs11942223 variants on serum urate and FEUA in response to fructose were present only in Caucasian ancestral subgroups but not in the Māori and Pacific ancestral subgroup. Conclusions: Variation in SLC2A9 influences acute serum urate and FEUA responses to a fructose load. SLC2A9 genotype may influence the development of gout on exposure to fructose-containing beverages, particularly in European Caucasian populations.